(untitled) (Al-NASR, 2024)
Man, a naturally inquisitive being, is profoundly emphasized by the holy Quran to observe the signs (ayat) of the Almighty in both the natural world and human existence, recognizing the interconnectedness of all the creation in the universe. This dual focus not only promotes a holistic approach to comprehending God but also reflects His unity and singularity (Tawhid). This research underscores the significance of acknowledging God’s signs and appreciating the interrelatedness of all the creations. It will not only enhance our spiritual development but will also be beneficial for the entire eco-system, reenforcing our role as the guardians of the natural world.